Pendampingan dan Pelatihan Penyusunan Peraturan Desa Candipari Sebagai Desa Wisata yang Sadar Hukum - Dandi Prasetiyo; Putri Narendra (CV. Era Digital Nusantara, 2024)
Candipari Village, located in Porong District, Sidoarjo, has developed itself into a tourist village with great potential in the tourism industry. However, the challenges in managing and regulating legal aspects in this context are crucial to supporting sustainability and sustainable village development. This study presents an approach to Assistance and Training in Preparing Village Regulations for Candipari Village as a Legally Aware Tourism Village. This method involves identifying relevant legal issues, preparing comprehensive training materials, as well as implementing simulations and active discussions to develop understanding and skills in legal drafting by a team of students who are guided and assisted by the University Legal Expert of 17 August 1945, namely Mr. Dr. Ahmad Solikhin Rusli, S.H., M.H., was the resource person for drafting tourist village regulations in Candipari Village, Sidoarjo.The results of this assistance show that the integration of better legal understanding has made a positive contribution to the sustainable management of tourism activities in Candipari Village. The active role of the Village Head and Village Consultative Body (BPD) in formulating village regulations also strengthens the policy framework that supports sustainable development and improves the quality of life of local communities. Furthermore, this approach not only increases the village's legal capacity, but also ensures that Candipari Village can optimally utilize its tourism potential while complying with applicable legal principles. This study provides an in-depth view of how legal assistance can be an important instrument in supporting the development of sustainable tourism villages in Indonesia.